Edukasi Penggunaan Google Form Untuk Evaluasi Program Unggulan Di SMAN 2 Abiansemal - Alam, Helmy Syakh; Putra, Anak Agung Gede Adi Mega; Dinata, Akbar Aditya; Saputra, I Putu Gede; Dananjaya, I Kadek Robert (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
The use of Google Form as an evaluation tool for flagship programs at SMA Negeri 2 Abiansemal was educated to enhance data-based feedback collection. This study was conducted using a design thinking approach, involving interviews, problem analysis with Miro Board, and the development and implementation of Google Form. The results revealed that traditional methods relying on parent meetings were considered less representative, while Google Form enabled structured, comprehensive, and anonymous data collection from students. Teacher satisfaction with the evaluation process significantly increased, highlighting the advantages of this technology-based solution. The implementation of Google Form not only simplified data analysis but also empowered the school to improve programs sustainably, aligning with the SDGs' goal of quality education.